Reduction in Synovitis Following Genicular Artery Embolization in Knee Osteoarthritis: A Prospective Ultrasound and MRI Study - Louise Hindsø; Per Hölmich; Michael M. Petersen; Jack J. Xu; Søren Heerwagen; Michael B. Nielsen; Robert G. C. Riis; Adam E. Hansen; Lene Terslev; Mikkel Taudorf; Lars Lönn (Diagnostics)
Background/Objectives: Genicular artery embolization (GAE) has demonstrated potential as a treatment for knee osteoarthritis by targeting inflammation and pain, although current evidence remains limited. This study used imaging biomarkers to objectively assess synovitis and possible ischemic complications following GAE. Methods: This was a prospective, single-center trial including participants with mild-to-moderate knee osteoarthritis. Ultrasound, contrast-enhanced (CE), and non-CE-MRI were performed two days before and one and six months after GAE. Ultrasound biomarkers included synovial hypertrophy, effusion, and Doppler activity. A combined effusion-synovitis score was assessed on non-CE-MRI, while CE-MRI allowed differentiation between synovium and effusion and was used to calculate whole-joint and local synovitis scores. The post-GAE MRIs were reviewed for ischemic complications. Results: Seventeen participants (aged 43–71) were treated. Significant reductions were observed in ultrasound-assessed synovial hypertrophy and Doppler activity, as well as in CE-MRI local and whole-joint synovitis scores. While reductions in effusion were noted in both ultrasound and MRI, these changes did not reach statistical significance. At one month, MRI revealed three cases of nonspecific osteonecrosis-like areas, which resolved completely by six months. Conclusions: This study demonstrated a reduction in synovitis and no permanent ischemic complication following GAE in knee osteoarthritis. Larger studies with longer follow-up are needed to confirm the long-term efficacy and safety of the procedure.